Gender in acceptance of augmented reality in e-commerce: An international perspective - Małgorzata Bartosik-Purgat; Wiktoria Rakowska (International Entrepreneurship Review)
Objective: The objective of the article is to answer research questions about the role of gender in the significance of factors (motives and risks) affecting the acceptance of augmented reality (AR) technologies by young international e-commerce consumers.